A new approach to the marine natural product ulapualide A - Kempson, James (2001)
This thesis describes synthetic studies directed towards a second generation total synthesis of ulapualide A. Ulapualide A is an extraordinary bioactive tris-oxazole based macrolide which was isolated from the egg masses of the marine sponge Hexabranchus sanguineus and exhibits potent antifungal activity with inhibition of leukaemia cell proliferation.